Internet Browsing Habits and Domain Choice Preferences of Economic Agricultural Engineers - Dövényi-Nagy, Tamás (Acta Agraria Debreceniensis, 2004)
The findings below are based on a questionnaire survey carried out in order to establish an internet-based service at the Center of Agricultural Sciences of Debrecen University: • The typical target group of the service in the short run with a weekly average of 5.9 hours on the web is more active than that for average Hungarian, adult Internet users. • A professional webportal with a searchable database, primarily incorporating an archive of organized agricultural news, articles, publications, fits well into the internet habits of the target group, which mainly consists of keyword-based information searces and browsing of the latest news. • The group prefers a short, easily recognizable domain name that refers to agriculture. Accents and foreign sounding words are not taken into account during selection. • As result of the choice from 43 eligible domains, the order would be the following: agrarunio, agroland, farmvilag, infoagro, farmland. • The names of magyargazda.hu, agrotrend.hu, agromester.hu, agronomus.hu are acceptable from the individual ideas.